2005
DOI: 10.1021/jf0404389
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin-Dependent Inhibition of Nitration Induced by Peroxidase/H2O2/Nitrite Systems in Human Saliva and Characterization of an Oxidation Product of Quercetin Formed during the Inhibition

Abstract: Local pH in the oral cavity can decrease to below 7 at the site where acid-producing bacteria are proliferating. Effects of pH on nitration of 4-hydroxyphenylacetic acid were studied using dialyzed human saliva. Dialyzed saliva nitrated 4-hydroxyphenylacetic acid to 4-hydroxy-3-nitrophenylacetic acid in the presence of nitrite and H(2)O(2). The rate of the nitration was dependent on pH, and the maximal rate was observed between pH 5.5 and 7.2. The optimum pH seemed to reflect rates of formation of nitrogen dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 37 publications
(63 reference statements)
2
33
0
Order By: Relevance
“…HNPA is excreted into the environment at concentrations that are an order of magnitude greater than the 3NTyr concentration (15,26) and so might be more available as a growth substrate than 3NTyr. Other studies have reported that mammalian peroxidases, including enzymes in human saliva, catalyze the nitration of 4-hydroxyphenylacetate to HNPA (9,29). On the other hand, the environmental flux of 3NTyr may be much higher than previously thought.…”
Section: Discussionmentioning
confidence: 85%
“…HNPA is excreted into the environment at concentrations that are an order of magnitude greater than the 3NTyr concentration (15,26) and so might be more available as a growth substrate than 3NTyr. Other studies have reported that mammalian peroxidases, including enzymes in human saliva, catalyze the nitration of 4-hydroxyphenylacetate to HNPA (9,29). On the other hand, the environmental flux of 3NTyr may be much higher than previously thought.…”
Section: Discussionmentioning
confidence: 85%
“…5). Quercetin radical can be transformed into 2-(3,4-dihydroxybenzoyl)-2,4,6-trihydroxy-3(2H)-benzofuranone (A) via the quinone (Hirota, Takahama, Ly, & Yamauchi, 2005). Quercetin 7-glucoside was also oxidized to A glucoside by nitrous acid (Morina, Takahama, Yamauchi, Hirota, & Veljovic-Jovanovic, 2015).…”
Section: Possible Reactions Of Polyphenols With Nitrite In the Stomachmentioning
confidence: 99%
“…However, Gunther et al [13] described a mechanism for NO-dependent tyrosine nitration that does not require the formation of highly reactive nitrogen oxide intermediates such as peroxynitrite or nitrogen dioxide. Peroxidases can also oxidize nitrite to nitrogen dioxide radical, which can cause nitration of tyrosine and tyrosine residues in proteins [14]. …”
Section: Introductionmentioning
confidence: 99%